Training Students to Ask Questions through Situation-Based Learning - I. Isrokatun,; Suhaebar, Imam; Purwono, Budi Sigit (International Journal of Psychosocial Rehabilitation, 2020)
Elementary school students have a high curiosity. This curiosity needs to be facilitated so that it can develop. However, what happens in the classroom is just the opposite, when elementary school students get older, the more reluctant they are asking. This results in the lack of courage to ask questions. This study aims at providing a clear picture and alternative to how to train and develop students’ skills in asking questions through Situation-Based Learning (SBL). This study employs the ADDIE method (Analyzing, Designing, Developing, Implementing, and Evaluating) that aims at illustrating how the SBL learning model can help training elementary students’ abilities and skills in asking questions. The subjects in this study were in 5th grade elementary school students ranging in age from 10 to 12 years. The results showed that the example of learning materials should be designed based on the characteristics SBL learning, and how the students’ response in asking questions. Therefore, it can be concluded that the students’ skills in asking questions were still relatively low, but could still be improved because the ability can to be trained and developed continuously through SBL learning with customized teaching materials. It is expected that the students have adequate asking skills, hence, they will be able to follow the trends of information and communication in this 4.0 era.